The The return-on-education gap between hispanics and non-hispanic whites - Sánchez-Soto, Gabriela; Bautista-León, Andrea; Singelmann, Joachim (Papeles de Población; Vol. 24 Núm. 98 (2018): Papeles de Población, 2019)
This paper analyzes differences in the return on education between non-Hispanic whites and four groups of Hispanics: Puerto Ricans, Mexicans, Cubans, and other Latin Americans. For Mexicans, Cubans, and other Latin Americans, we also distinguish between native-born in the U.S. and foreign-born immigrants. We use data from the American Community Survey 2008-2013 to estimate the differences in the return on education by comparing income relative to educational attainment across ethnic and immigrant groups. The analyses account for age, education, English skills, citizenship status, union status, year, metro area residence, and region of residence, as well as time spent in the U.S. for the foreign-born. We find that the returns on schooling are lower for Hispanics relative to NH whites, but that there is also a gap in earnings between U.S. and foreignborn Hispanics. The loss of wages experienced by Hispanic immigrants is greater at higher levels of education, and for women.